Reviewing the implementation of the voluntary disclosure program as a database provider in exploring the potential of income tax article 25/29 for high-wealth individuals: Case Study: KPP Madya Dua Medan - Setiawan, Benny; Sianipar, Yackobus Sahat Martua (Educoretax, 2024)
This research is conducted to determine the role of the Voluntary Disclosure Program (PPS) in providing a database to the Directorate General of Taxes in extracting the potential of Income Tax Article 25/29 on Individual Taxpayers with the High Wealth Individual (HWI) category.  This study also aims to determine the condition of income tax Article 25/29 of Individuals at KPP Madya Dua Medan and the obstacles in the application of PPS in extracting the potential of Income Tax Article 25/29 of Individuals. The method used in this research is qualitative method by conducting interviews, documentation and literature study. Interviews were conducted with employees of the Directorate General of Taxes and academics. Documentation is done on the data provided by KPP Madya Dua Medan. The reference sources used were obtained from journal provider platforms on the internet. The results of this study indicate that PPS can provide a database for the activities of extracting the potential of ITA 25/29 of HWI WPOP. The obstacles to the use of PPS data are the misalignment of information on the use of data between the DGT head office unit and the vertical unit, the communication between tax officers and taxpayers, the exploration of the potential of HWI which is still partial, and the tax planning of HWI taxpayers. Keywords: Extracting Potensial, Income Tax Article 25/29 on Individual Taxpayers, Voluntary Disclosure Program, High Wealth Individual, KPP Madya Dua Medan.